Human Activities can affect Human Lungs and Breathing? (Matter of Public Health) - Calhoun, Nicole; Sharma, Dipti (European Journal of Applied Sciences, 2021)
This study explores Applied Physics showing how Physics is involved in human breathing and how it can help human towards their personal care about lung health. This work reports the change observed in speed, acceleration, and kinetic energy of human lungs during normal and conditioned breathing for multiple participants under several physical conditions to compare results of human breath in terms of human lung movements. It further gives the information of how time period, frequency of human breath, angular speed of lungs changes based on human activities and the value of force required by lungs for breathing change. The effect of physical exercise on human lung is also reported here in terms of power dissipation and spring constant of the lungs. This study shows a novel way of studying the Physics behind human lungs and breathing that can help human towards personal care in real life. It also shows how human breathing can affect public health in terms of their lifestyle and lung’s types.